Strategi Inovasi dan Keberlanjutan Bisnis bagi Wirausaha Muda Gen Z - Pamungkas, Giantoro; Sulistiana, Indra; Mutiara, Rini; Aldiano, Rival (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aimed to enhance vocational students' understanding of innovation, sustainability, and profitability in entrepreneurship. The topic was chosen due to the low entrepreneurial literacy among Gen Z students, particularly in financial management and sustainable business planning. The methods used included interactive lectures, group discussions, business simulations, and pre- and post-activity evaluations. The results showed a significant improvement in students’ understanding, especially in basic financial management and developing innovative, eco-friendly business ideas. Student participation was high, and most groups successfully created simple business plans with projected profits. This activity demonstrated that participatory educational approaches are effective in shaping an adaptive, strategic, and sustainable entrepreneurial mindset among students. These findings highlight the importance of continuing similar programs to support the growth of a youth entrepreneurship ecosystem starting from the school level.